Using Alkylammonium Salt to Enhance the Adsorption Potential for Ca-Montmorillonite Clay to Remove Color Effluent from Wastewater - AL-Mammar, Dunya Edan; Salim, Rasha Tariq; AL-Shammari, Noor Hussein (Indonesian Journal of Chemistry, 2025)
Ca-montmorillonite raw clay (Ca-M) was modified using two different alkylammonium salts, tetramethylammonium iodide (MT) clay, tetrabutylammonium iodide (BT) clay, and used as an adsorbent to remove Biebrich scarlet (BS) dye from wastewater in batch mode. Clay samples were analyzed using an atomic force microscope (AFM), Fourier transform infrared spectroscopy (FTIR), and X-ray diffraction (XRD). The effects of operating parameters affecting the adsorption of BS dye onto clay samples were studied, such as clay weight, adsorption period, initial BS concentration, temperature, and pH. The experimental data were analyzed using Langmuir and Freundlich adsorption isotherm models; the obtained values of correlation coefficient R2 showed that the adsorption followed the Freundlich isotherm model. Thermodynamic data reveal that the adsorption of BS dye onto BT and MT clay samples is exothermic and occurs spontaneously with a decrease in disorder. In contrast, the adsorption of this dye onto raw clay is endothermic and occurs spontaneously with an increase in disorder. The lower values of enthalpy change refer to the adsorption process as physisorption type. The results of kinetics analysis for the adsorption process showed that the pseudo-second-order model was more suitable to represent the adsorption process than the pseudo-first-order model.